Discoveries and identification methods of metal oxalates in lichens and their mineral associations: A review of past studies and analytical options for lichenologists. (March 2023) - Krajanová, Viktória
Abstract: Lichens are generally acknowledged as the main agents of the initial bioweathering of rock substrates. The most direct evidence of a chemical interaction between lichens and their mineral substrata is the production of oxalic acid, of which interaction with ions present in a close lichen environment occasionally results in the precipitation of metal oxalates. In the past, only a few studies revealed the presence of metal oxalates in lichens, and currently, almost no new discoveries are arriving. Therefore, the main goal of this review is to bring the focus back to this phenomenon. To date, only Mg oxalate dihydrate, Mn oxalate dihydrate, Cu oxalate hemihydrate, Zn oxalate dihydrate, and anhydrous Pb oxalate have been detected in lichens. The most reliable diagnostic methods of metal oxalates in lichens are powder X-ray diffraction (pXRD), infrared spectroscopy (IR), extended X-ray absorption fine structure (EXAFS) spectroscopy, and Raman spectroscopy. Prospective lichen specimens for investigations may be found in anthropogenically-polluted environment or naturally metal-rich rock substrata. This review acts as an initial guide that provides analytical options for field lichenologists, offers a few suggestions for further research on this matter, and encourages to new biomineral discoveries in the scope of mineralogy. Survival in the metal-toxic environment, ability to produce oxygen, and extremophile nature, are the reasons why lichens are good subjects for research within the context of currently expanding astrobiology sciences, as well. Graphical abstract: Image 1 Highlights: Metal oxalates can be discovered in lichens from metal-rich mineral environments. Metal oxalates can be discovered in lichens from anthropogenically polluted environments. The best methods to identify metal oxalates in lichens are pXRD, IR, EXAFS, and Raman spectroscopy. Currently, not many new discoveries of metal oxalates are arriving from lichens. New metal oxalate biomineral species could be described from lichens.